Twist Sensor Based on Long Period Grating and Tilted Bragg Grating Written in Few-Mode Fibers - Kang Yang; Yange Liu; Zhi Wang; Yan Li; Ya Han; Hongwei Zhang (IEEE Photonics Journal, 2018)
A twist sensor based on a few-mode long period grating (LPG) and a tilted fiber Bragg grating (TFBG) is proposed and demonstrated. The LPG, inscribed in a step index few-mode fiber by a CO2 laser, is utilized to excite the LP11 core mode. The followed TFBG written in graded index a few mode fiber with the LP11 core mode as exciting light is served as sensing element. By analyzing transmitted intensity difference of two dips in transmission spectrum of the TFBG induced by the mode couplings from forward-propagating LP11 core mode to backward-propagating LP11 and LP21 core modes, a twist sensitivity of 1.074 dB/(rad/m) from −5.23 rad/m to 5.23 rad/m is achieved. The proposed sensor has advantages of easy operation and simple structure.